Extensions of linear cycle sets and cohomology - Guccione, J.A.; Guccione, J.J.; Valqui, C. (Springer Science and Business Media Deutschland GmbH, 2023)
We generalize the cohomology theory for linear cycle sets introduced by Lebed and Vendramin. Our cohomology classifies extensions of linear cycle sets by trivial ideals, whereas the cohomology of Lebed and Vendramin only deals with central ideals I (which are automatically trivial). Therefore our theory gives an analog to the theory of extensions of braces by trivial ideals constructed by Bachiller, but from a cohomological point of view. We also study the general notions of extensions of linear cycle sets and the equivalence of extensions.
Keywords: Linear cycle sets; Extensions; Cohomology; https://purl.org/pe-repo/ocde/ford#1.01.01